Analisis Resource Based View (RBV) Dalam Menciptakan Keunggulan Kompetitif (Studi Kasus: UMKM Mie Jebew BDL) - Dwi Ipana; Faza Alfa Nuha; Vicky F Sanjaya (Universitas Muhammadiyah Sumatera Utara, 2026)
This study focuses on the analysis of resource-based strategy (RBV) and its role in building competitive advantage for a spicy culinary MSME, Mie Jebew BDL in Bandar Lampung. A descriptive qualitative approach was used as the research method, with data collected through direct observation, in-depth interviews, and document analysis. The findings indicate that Mie Jebew BDL's success in maintaining its position amidst market competition depends heavily on the synergy between tangible and intangible asset management. Tangible assets include premium quality raw materials and efficient kitchen operations, while intangible assets include creative flavor innovations, a strong brand image, and good relationships among owners, staff, and consumers. Adaptability to market dynamics and continuous organizational learning are also identified as vital keys to maintaining long-term competitive advantage. The study concludes that culinary MSMEs achieve sustainable advantage through the management of internal resources that exhibit the characteristics of being strategically valuable (valuable), rare (rare), inimitable (hard to replicate), and non-substitutable (non-substitutable).